Secondary forest enrichment as a technology for sustainable production for family agriculture - Brienza Júnior, Silvio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2012)
Traditional slash-and-burn agriculture can be improved by planting fast growing leguminous trees to help accumulate biomass and nutrients during the fallow phase, and thus, improve productivity during the next phase of agriculture. Experimental work has demonstrated that Acacia mangium (acácia), Inga edulis (ingá), Acacia angustissima (ligeirinha) and Sclerolobium paniculatum (taxi-branco) when planted with crops (maize and cassava), at density of 2 m x 2 m, can result in increases in tree survival, biomass production and wood volume. The biomass stocks in trees can vary from 35-40 t ha-1 (acácia) to 10-15 t ha-1 (taxi-branco). In three years (one year of cropping + two years of enriched fallow) the enriched fallow system results in a biomass accumulation equivalent to up to five years of traditional fallow.